Efektivitas Program Promosi Kesehatan Berbasis Komunitas dalam Menurunkan Faktor Risiko Hipertensi di Praya Lombok Tengah - Zikri, Lia Novia; Gufron, Ahmad (Journal of Applied Health Sciences, 2026)
Hypertension remains one of the major public health problems contributing significantly to increased morbidity and mortality from cardiovascular diseases, particularly in developing countries such as Indonesia. Low levels of community knowledge, unhealthy lifestyle behaviors, and limited implementation of promotive and preventive approaches at the community level pose major challenges to hypertension control. Therefore, community-based health promotion programs are considered a potential strategy to reduce hypertension risk factors through community empowerment and active participation. This study aims to analyze the effectiveness of a community-based health promotion program in reducing hypertension risk factors among adults in Praya, Central Lombok Regency. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed. The study sample consisted of adult community members who participated in the entire series of community-based health promotion activities. Data were collected using structured questionnaires to assess knowledge and health-related behaviors, as well as measurements of systolic and diastolic blood pressure before and after the intervention. Data analysis was conducted using descriptive statistics and paired statistical tests. The results showed a significant increase in community knowledge regarding hypertension and its risk factors after the intervention. Positive changes in health behaviors were also observed, including reduced salt intake, increased physical activity, and improved awareness of regular blood pressure monitoring. Clinically, the program resulted in a statistically significant reduction in both systolic and diastolic blood pressure among participants. The discussion indicates that the effectiveness of the program was influenced by its participatory approach, social support within the community, the involvement of community health cadres, and the alignment of the intervention with local sociocultural contexts. The community-based health promotion program successfully bridged improvements in knowledge with behavioral changes that produced tangible health outcomes. In conclusion, community-based health promotion programs are effective in reducing hypertension risk factors and have strong potential as sustainable promotive and preventive strategies for controlling non-communicable diseases at the local level. These findings support the strengthening and integration of community-based programs into local health policies to improve population health outcomes.